Usefulness of Topically Applied Sensors to Assess the Quality of 18F-FDG Injections and Validation Against Dynamic Positron Emission Tomography (PET) Images - Lattanze, Ronald K.; Osman, Medhat M.; Ryan, Kelley A.; Frye, Sarah; Townsend, David W. (Frontiers in Medicine, 2018)
Background: Infiltrations of 18F-fluorodeoxyglucose (FDG) injection affect positron emission tomography/computed tomography (PET/CT) image quality and quantification. A device (Lucerno Dynamics, Cary, NC) using scintillation sensors generates time-activity curves (TACs) during the uptake period to identify and characterize radioactivity near the injection site prior to patient imaging. The aim of this study was to compare sensor TACs with injection quality as assessed from dynamic PET imaging during the uptake period. Methods: Subjects undergoing routine FDG PET/CT imaging were eligible for this IRB-approved prospective study. After providing informed consent, subjects had sensors topically placed on their arms. FDG was injected into subjects’ veins directly on the PET imaging table. Dynamic images were acquired of the injection sites during the uptake period. These dynamic image acquisitions and subjects’ routine standard static images were evaluated for abnormal FDG accumulation near the injection site. Images were interpreted by nuclear medicine physicians. TACs were interpreted independently by Lucerno staff. Dynamic image acquisition interpretation results were compared to the TAC interpretations. Static image interpretations were also compared to dynamic image acquisition interpretations. Results: Dynamic image acquisitions and TAC interpretations were compared for 21 subjects. Physicians interpreted 4 subjects with no FDG accumulation at the injection site, whereas 17 showed evidence of accumulation. TAC interpretations agreed with the dynamic images interpretations in 18/21 (86%) subjects. In 3/21 cases dynamic images showed minor activity at the injection site not seen from the TACs. Static image interpretation was in agreement with dynamic images interpretation in 11/21 (52%) subjects. In 10/17 cases where dynamic image acquisition showed FDG accumulation, the FDG presence at the injection site resolved completely during uptake corresponding to venous stasis, the temporary sequestration of blood from circulation. Conclusions: TACs are an effective way to identify and characterize infiltrations and venous stasis. Comparable to an infiltrate, a venous stasis may produce spurious and clinically meaningful measurement bias and possibly even scan misinterpretation. Since the quality and quantification of PET/CT studies are of clinical importance, TACs acquired during the FDG uptake may prove to be a useful quality control measure to reduce infiltration rates and potentially improve patient care.